Bortezomib for anti-NMDAR encephalitis following daclizumab treatment in a patient with multiple sclerosis. Issue 1 (18th May 2021) - Karunaratne, Kushan; Ahrabian, Dariush; Monaghan, Bernadette; Campion, Tom; Yousry, Tarek; Lunn, Michael P; Zandi, Michael S; Howard, Robin S; Kullmann, Dimitri M; Spillane, Jennifer; Walker, Matthew; Chataway, Jeremy
Abstract : Background: Daclizumab is an anti-CD25 monoclonal antibody developed for the treatment of relapsing remitting multiple sclerosis, which was withdrawn worldwide in March 2018, due to emerging serious immune-mediated systemic andcentral nervous system adverse events. We report a case of anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis occurring 14 weeks after stopping daclizumab, which responded to the proteasome inhibitor bortezomib. Methods: Following lack of effective clinical response to first line (corticosteroid, plasma exchange, intravenous immunoglobulin) and second line (rituximab) treatments, bortezomib therapy was commenced. The patient received six cycles of bortezomib treatment. Results: Clinical improvement was noted 4 weeks after the first of six cycles of bortezomib and the patient experienced sustained clinical improvement. Conclusion: Our case provides further class IV evidence of the use of bortezomib therapy for treatment refractory anti-NMDAR encephalitis.